Increasing the Diversity of the Teacher Workforce: Socio-Political Challenges to Reducing Inequalities in Access to Teacher Education Programs - Pit-ten Cate, Ineke M.; Rivas, Salvador; Busana, Gilbert (Frontiers in Education, 2021)
Cross-border migration leads to a diversification of societies, which is reflected in the education system, where classrooms are composed of students with heterogeneous cultural, linguistic, socio-economic characteristics. However, this diversity is only to a limited extent reflected in the teacher population, even though teachers from different backgrounds can bring specific intercultural competencies, have more positive attitudes toward multicultural heterogeneity and act as role models. To facilitate the diversification of the teaching profession, it is imperative that the cohorts of students entering teacher education programs represent the diversity of societies, however studies have shown students with migration backgrounds or from families with lower socio-economic status are underrepresented in such programs. This study considered the demographic constellation of applicants for admission into the teacher education program in Luxembourg (2015-2019) and investigated to what extent the admission process (dis)advantages certain groups. Results revealed that although applications come from diverse backgrounds, proficiency in the country´s native languages poses a disadvantage for students with migration backgrounds. In addition, applicants coming from more privileged families stand a better chance of being admitted. Results are interpreted within the framework of social mobility and social reproduction. Implications for the admission to the teachers´ education program are discussed.